An innovative method for exhaust gases toxicity evaluation in the miniature turbojet engine. Issue 6 (2nd October 2017) - Gawron, Bartosz; Białecki, Tomasz; Janicka, Anna; Górniak, Aleksander; Zawiślak, Maciej
Abstract : Purpose: The purpose of this paper is to present an assessment method of the toxicity emission evaluation during combustion in the miniature turbojet engine. Design/methodology/approach: A small-scale turbojet engine was used for the research because measurements on real aircraft turbines are complex and expensive. The experiment was performed in accordance with innovative BAT – CELL Bio – Ambient Cell method which consists of determination of virtual toxic impact of the gas mixture on the living cells; it is therefore a direct method. The most significant innovation of this method is that, during the test, which consists of exposing the cells to the gas mixture, the cells are deprived of culture fluid. Findings: The preliminary analysis shows that the method used here allows to determine the virtual impact of the gases on the human respiratory system and skin. It could be useful in defining the arduousness of an airport. The obtained results show that both of exhaust gases represent similar toxicity. Practical implications: The new in vitro method allows to determine the virtual impact of the gases on the human respiratory system and skin. Significant potential for further research not only on the miniaturised engines, but also in the case of real objects, as this method does not have to be performed in a laboratory. Originality/value: The work presents potential application of the innovatory method for exhaust gases toxicity evaluation in jet engines, which could be useful in defining the arduousness of an airport.